Heterogeneity of hydrate-bearing sediments: Definition and effects on fluid flow properties - Kou, Xuan; Li, Xiao-Sen; Wang, Yi; Liu, Jian-Wu; Chen, Zhao-Yang (Energy, 2021)
Heterogenous distribution of gas hydrate in pores is the common characteristic of hydrate formation at various experimental scales. In this work, in order to fill the gap of defining the hydrate phase heterogeneity degree of hydrate-bearing sediments, we conduct a series of pore-scale experiments and simulations on hydrate formation behaviors and two-phase flow properties in hydrate-bearing samples by micro X-ray CT. The enhanced heterogeneous distribution of gas hydrate in small pores has been observed from experimental results, suggesting that the degree of hydrate heterogeneity in sandy or silty sediments may be underestimated. Therefore, the definition of hydrate heterogeneity degree is firstly proposed to characterize the hydrate phase heterogeneity of hydrate-bearing sediments. Additionally, we further investigate the effects of hydrate heterogeneity on fluid flow properties by introducing three types of hydrate distribution in porous media, which are homogeneous, clogging, and clumpy distribution. The clogging type of hydrate distribution could result in the sharply increased rate of permeability reduction, while the clumpy type of hydrate distribution might result in the declined rate of permeability reduction. Meanwhile, the heterogenous hydrate distribution leads to the rapid decrease in gas relative permeability. These findings are significant for laboratory studies and gas recovery in field tests. (c) 2021 Elsevier Ltd. All rights reserved.